Dampak Melewatkan Sarapan pada Remaja - Kasenda, Telvie Laura; Arief, Yuni Sufyanti; Indarwati, Retno; Yunara, Yulia (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to analyze scientific articles that examine the impact of skipping breakfast on adolescents. The method used is a systematic review and The Preferred Reporting Items for Systematic Review and Meta Analysis (PRISMA) is used as a guideline. The results of this study indicate that skipping breakfast has a negative impact on cognitive performance and academic achievement in adolescents. In addition, it can also increase the risk of more serious health conditions such as cardiometabolic disorders and other non-communicable diseases along with adolescent development. Conclusion, breakfast is one of the important factors in adolescent health and development, so skipping breakfast will have a negative impact on adolescents. Intervention strategies are needed from the individual, family, school, and government levels in improving adolescent nutrition. Keywords: Academic Achievement, Adolescent, Breakfast Skipping, Cognitive Performance